Enhancing financial inclusion in Nigeria: the role of Islamic finance - Abdullahi, Abdurrahman; Othman, Anwar Hasan Abdullah; Kassim, Salina (Smart Ever Konferans Organizasyon Limited, 2020)
Financial inclusion helps in reducing extreme poverty, supporting inclusive development, and enhancing the well-being of the people. As a result, policy makers, regulators and development institutions have made financial inclusion a priority in promoting economic growth and reducing poverty and inequality. One important channel used in promoting access to finance among the poor is Islamic finance. This paper, therefore, reviewed theory and literature in order to synthesize the role of Islamic finance in enhancing financial inclusion. The review revealed that Islamic finance helps in ensuring financial inclusion through the provision of Shariah compliant, risk-sharing financial products and services. In addition, the Islamic social finance products such as Zakah, Sadaqah and Waqaf compliments the commercial aspects. Consequently, Islamic finance helps in reducing voluntary financial exclusion and extreme poverty. The paper also highlighted the role of government in promoting financial inclusion through the development of appropriate regulatory and supervisory frameworks, financial inclusion strategies, protecting consumers and advancing financial literacy. The paper recommends the sustained application of risk-sharing financial products by Islamic financial institutions in Nigeria. In addition, Islamic banks should complement their financing products with Zakah, Sadaqah and Waqaf. Furthermore, government should sustain its efforts towards consumer education and financial literacy.